PENGARUH FORMULASI BREAKFAST CEREAL FLAKES BERBASIS TEPUNG BERAS MERAH (Oryza nivara) DAN TEPUNG SAGU (Metroxylon sp) TERHADAP PENILAIAN ORGANOLEPTIK DAN FISIKOKIMIA - Umar, Muhammad Isfan; ansharullah, ansharullah; Sadimantara, Muhammad Syukri (Jurnal Sains dan Teknologi Pangan, 2018)
ABSTRACT The purposes of this study were to determine the effect of formulations of red rice flour and sago flour on organolepticcharacteristics, physical properties and nutritional content of breakfast cereal flakes. This study used a CompletelyRandomized Design (CRD) with 3 replications. Formulations of comparison of red rice and sago flour were F1 (90% RedRice Flour: 10% Sago Flour), F2 (70% Red Rice Flour: 30% Sago Flour), F3 (50% Red Rice Flour: 50% Sago Flour) ), F4(30% Red Rice Flour: Sago Flour 70%), F5 (10% Red Rice Flour: 90% Sago Flour). The formulation of red rice and sagoflour had very significant effect (p <0.05) on physical properties (water absorption) and nutritional value (ash content, fatcontent, fiber content, energy content) while significantly affected on water content (p <0 05) and there was no significanteffect on protein and carbohydrate contents (p <0.05). Antioxidant activity of cereal flakes breakfast increased as long as theincreasing of addition of sago flour. Breakfast cereal flakes red rice flour and sago had nutritional value according to SNIstandard and based on organoleptic assessment, the product was accepted by panelist. Keywords: Flourred rice, flour sago, breakfast cereal flakes. ABSTRAK Tujuan penelitian ini adalah untuk mengetahui pengaruh berbagai formulasi tepung beras merahdan tepung sagu terhadapnilai organoleptik, sifat fisik dan kandungan gizi breakfast cereal flakes. Penelitian ini menggunakan Rancangan AcakLengkap (RAL) dengan 3 ulangan. Formulasi perbandingan tepung beras merah dan tepung sagu antara lain F1 (TepungBeras Merah 90% : Tepung Sagu 10%), F2(Tepung Beras Merah 70% : Tepung Sagu 30%), F3 (Tepung Beras Merah 50%: Tepung Sagu 50%), F4 (Tepung Beras Merah 30% : Tepung Sagu 70%), F5 (Tepung Beras Merah 10% : Tepung Sagu90%). Formulasi tepung beras merah dan sagu berpengaruh sangat nyata (p<0,05) terhadap sifat fisik (daya penyerapanair) dan nilai gizi (kadar abu, kadar lemak, kadar serat, kandungan energi), berpengaruh nyata terhadap kadar air (p <0,05)dan berpengaruh tidak nyata terhadap kadar protein dan karbohidrat (p<0,05). Aktivitas antioksidan breakfast cereal flakesmeningkat seiring dengan meningkatnya penambahan tepung sagu. Breakfast cereal flakes tepung beras merah dan sagumemiliki nilai gizi sesuai standar SNI dan berdasarkan penilaian organoleptikdapat diterima (disukai) oleh panelis. Kata kunci: Tepung beras merah, tepung sagu, breakfast cereal flake.